Engineering lignin-incorporated hydrogels for agricultural and environmental applications: From synthesis to sustainable implementation - Fuke Ai; Xiaolei Zhang; Bing Hu; Shin Ying Foong; Weidong Ye; Yameng Li; Quanguo Zhang; Pedram Fatehi; Siming You; Zhiping Zhang (Bioresource Technology, 2026)

Stability of oil bodies under pulsed electric field exposure to rapeseed: New insights into improving oil extraction capacity - Qiqi Zhang; Jinling Hu; Yunyun Li; Bo Wang; Jing Wang; Jie Zhao; Siming Zhao; Caihua Jia; Jie Kuai; Guangsheng Zhou (Food Chemistry, 2026)

Increased microbiological risks caused by extreme precipitation in a drinking water system in mountainous area: From source to tap - Xinyan Xiao; Chen Cheng; Xiuxiu Wang; Ziqi Luo; Lihua Li; Siming Hu; Dongmei Zhu; Mingbao Feng; Chengsong Ye; Xin Yu (Journal of Hazardous Materials, 2026)

Revealing long-term runoff mechanisms using the deep learning model interpretable framework driven by global and local information - Binlin Yang; Lu Chen; Siming Li; Bin Yi; Nengjie Hu (Journal of Hydrology, 2025)

A thermal-pore-chemical-mechanics model for large landslides in the unsaturated case - Huanhuan Zhang; Wei Liu; Siming He; Xiong Tang; Wei Hu (Bulletin of Engineering Geology and the Environment, 2025)

Bibliometric and visual analysis of drug-specific immunotherapy from 1990 to 2024 - Zhengjiu Cui; Xiaorui Chen; Siming Zhai; Yuanyuan Wang; Chanchan Hu; Bin Yuan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Discovery of potent MD2 inhibitors by hierarchical virtual screening strategy and bioactivity evaluation - Lili Yang; Jialu Liu; Lei Di; Siming Tang; Ping Hu; Fang Wang; Zeng Li (Chemico-Biological Interactions, 2025)

Genetic analysis and fine mapping reveal that AhRt3, which encodes an anthocyanin reductase, is responsible for red testa in cultivated peanuts - Yanyan Tang; Xiantao Zhou; Xin Li; Cai Zhou; Wenlin Wang; Mo Zhou; Zhicheng Hu; Xiaobei Li; Kaiyuan Zhang; Siming Wang; Zhihao Zhang; Hao Chen; et al. (Theoretical and Applied Genetics, 2025)

Brazilin alleviates acute lung injury via inhibition of ferroptosis through the SIRT3/GPX4 pathway - Xiaopei Yan; Li Xu; Chang Qi; Yiling Chang; Juanjuan Zhang; Ning Li; Baoyu Shi; Bo Guan; Siming Hu; Chao Huang; Hui Wang; Ying Chen; et al. (Apoptosis, 2025)

Characteristics of Dissolved Inorganic Carbon (DIC) in the Western Coast of the Taiwan Strait Using a Shipboard Measurement - Jiehua Hu; Jinpei Yan; Hang Yang; Siming Huang; Siying Dai; Xiaoke Zhang; Shanshan Wang; Shuhui Zhao (Journal of Marine Science and Engineering, 2024)
An online dissolved inorganic carbon (DIC) monitoring system was produced to achieve high spatial and temporal resolution in DIC data from the western Taiwan Strait (WTS) during the summer. Surface seawater DIC, salinity, dissolved organic carbon (DOC), Chl-a, and NO3− samples were collected, as well as the vertical profiles of DIC, to understand DIC variations in the WTS. The results showed that the range of DIC levels in the surface seawater from the WTS was from 1.68 to 2.21 mmol/L (Mmol), with an average of 1.93 ± 0.19 Mmol, which was consistent with the sampling results using titration determination, with an average of 1.98 ± 0.12 Mmol. A high correlation (R2 = 0.96) was presented between the online monitoring and sampling detection of DIC, indicating that DIC could be measured with high accuracy using the online monitoring system. The spatial distribution of DIC was similar to that of salinity, but it was different from that of DOC and Chl-a. The DIC concentration positively correlated with salinity (R2 = 0.51) and presented a negative correlation (R2 = 0.92) with seawater temperature. However, the surface seawater DIC was almost independent from DOC and Chl-a in the observation sea areas. The DIC levels first increased and then decreased with the depth, with the highest DIC concentration occurring in the subsurface water at about 10 m, which was similar to the profiles of salinity and Chl-a in the northern and southern areas of the WTS. The profiles of DIC, salinity, NO3−, and Chl-a were almost independent from the water depth in the central WST. This indicated that seawater DIC in the WTS was mainly affected by seawater temperature, salinity, and the vertical mixing of sea water, but it was less impacted by TOC and Chl-a.

A Thermo-Poro-Mechanics Model Predicts the Transition from Creep to Rapid Movement of Large Landslides - Huanhuan Zhang; Wei Liu; Siming He; Wei Hu (Rock Mechanics and Rock Engineering, 2024)

The pivotal role of secondary nutrients and micronutrients in regulating fruit quality and root exudates metabolism profile of citrus - Yanni Tang; Wei Lou; Xiang Yan; Shiqian Li; Pengwei Wang; Yingjie Zhou; Ting Zhan; Siming Zhang; Chengxiao Hu; Xu Wang; Hanliang Liu; Qiling Tan; et al. (Plant and Soil, 2024)

Study by means of 1H nuclear magnetic resonance of the oxidation process in high oleic sunflower oil and palm oil during deep-frying of fish cakes - Xiaoyu Luo; Benlun Hu; Caihua Jia; Ru Liu; Jianhua Rong; Siming Zhao; Meng Niu; Yan Xu; Tao Yin; Juan You (Food Research International, 2024)

Creep-to-Runout Transition of Large Landslides Controlled by Frictional Velocity Strengthening and Weakening (Vajont 1963, Italy) - Huanhuan Zhang; Siming He; Wei Liu; Yu Deng; Wei Hu (Rock Mechanics and Rock Engineering, 2023)

The impact of GmTSA and GmALS on soybean salt tolerance: uncovering the molecular landscape of amino acid and secondary metabolism pathways - Minghao Sun; Siming Wei; Jiarui Liu; Luyao Wang; Yu Zhang; Limin Hu; Jingxi Piao; Zhao Liang; Hongwei Jiang; Dawei Xin; Ying Zhao; Qingshan Chen; et al. (Theoretical and Applied Genetics, 2023)

Free-standing high-entropy alloy plate for efficient water oxidation catalysis: structure/composition evolution and implication of high-valence metals - Lingya Yi; Siming Xiao; Yunpeng Wei; Dazhi Li; Rongfei Wang; Shengfeng Guo; Weihua Hu (Chemical Engineering Journal, 2023)

Power performance of an asymmetric wave energy converter near a partial reflection wall - Binzhen Zhou; Qi Zhang; Jianjian Hu; Peng Jin; Hengming Zhang; Siming Zheng (Ocean Engineering, 2023)

Role of the in-situ-produced dextran by lactic acid bacteria in the texture modification of pea flour pastes - Jike Shuai; Lingyan Zhang; Zhimin Hu; Caihua Jia; Meng Niu; Siming Zhao; Yan Xu (Food Research International, 2023)

Fasudil attenuates glial cell-mediated neuroinflammation via ERK1/2 and AKT signaling pathways after optic nerve crush - Wei Huang; Qianqian Lan; Li Jiang; Wenya Yan; Fen Tang; Chaolan Shen; Hui Huang; Haibin Zhong; Jian Lv; Siming Zeng; Min Li; Zhongxiang Mo; et al. (Molecular Biology Reports, 2020)

In honor of Professor Robert P. Hanzlik on the occasion of his retirement - Siming L. Wang; Longqin Hu; Binghe Wang (Medicinal Chemistry Research, 2020)

Erratum to: Xeno-repopulation of Fah−/−Nod/Scid mice livers by human hepatocytes - BaoLiang Su; ChangCheng Liu; Dao Xiang; HaiBin Zhang; SiMing Yuan; MinJun Wang; Fei Chen; HaiYing Zhu; ZhiYing He; Xin Wang; YiPing Hu (Science China Life Sciences, 2011)

Xeno-repopulation of Fah−/−Nod/Scid mice livers by human hepatocytes - BaoLiang Su; ChangCheng Liu; Dao Xiang; HaiBin Zhang; SiMing Yuan; MinJun Wang; Fei Chen; HaiYing Zhu; ZhiYing He; Xin Wang; YiPing Hu (Science China Life Sciences, 2011)